Geopoetics of Belozerye in Book ‘Journey to Kirillo-Belozersky Monastery’ by S. P. Shevyrev - O. N. Aleksandrova-Osokina; You Juan Wang (Научный диалог)
The article analyzes S. P. Shevyrev’s book ‘Journey to Kirillo-Belozersky Monastery’ and focuses on the geopoetics of the Belozerye region. The novelty of the study lies in its use of geopoetic paradigm as a tool for analysis and its examination of a relatively understudied work. The relevance of the study is due to the growing interest in literary geography. The article presents an exploration of the spatial and sacred imagery of Belozerye as a local text of Russian North. It argues that Shevyrev’s geopoetic image of Belozerye is characterized by two distinctive features: ‘frontier’ and ‘sacredness’. The former highlights the region as a cultural and territorial ‘frontier’ of Russia, while the latter portrays it as a spiritual center, the ‘heart’ of Russian spiritual and religious culture. The authors of the study emphasize that this antinomic pair constitutes a characteristic feature of Belozerye as a local text of Russian culture. The article also examines the poetics of geographical (landscape) and sacred (monastery, church) objects in Shevyrev’s book, emphasizing how the discovery of the value-laden content of geocultural imagery contributes to the formation of artistic generalization.